The Frontal and Cerebellar Metabolism Related to Cognitive Dysfunction in Multiple System Atrophy - Shen, Cong; Chen, Qi-Si; Zuo, Chuan-Tao; Liu, Feng-Tao; Wang, Jian (Frontiers in Aging Neuroscience, 2022)
Background: Cognitive dysfunctions have been reported in multiple system atrophy (MSA). However, the underlying mechanisms remain to be elucidated. This study aimed to explore the possible cerebral metabolism associated with domain-specific cognitive performances in MSA. Methods: Eighty-four patients were diagnosed as probable or possible MSA, comprised of 27 patients as MSA with predominant parkinsonism (MSA-P) and 57 patients as MSA with predominant cerebellar ataxia (MSA-C). The comprehensive neuropsychological tests and 18F-fluorodeoxyglucose (18F-FDG) Positron Emission Tomography (PET) imaging were performed. Z-score was calculated to nondimensionalize and unify indicators of different tests in the domains of executive function, attention, language, memory and visuospatial function. Correlations between specific Z-score and cerebral 18F-FDG uptake were analyzed using statistical parametric mapping. The cognition-related metabolic differences between patients with MSA-P and MSA-C were analyzed by post-hoc test. Results: Z-scores of the domains including attention, executive function and language correlated positively with the metabolism in the superior/ inferior frontal gyrus and cerebellum, but negatively with that in insula and fusiform gyrus (P<0.001). No significant differences on neuropsychological performances and frontal metabolism were found between MSA-P and MSA-C patients. Only lower metabolism in cerebellum was observed in MSA-C. Conclusion: Metabolic changes in frontal lobe and cerebellum may participate in the cognitive impairments of patients with MSA. Nevertheless, cognitive and corresponding metabolic differences between the two subtypes of MSA still need more exploration.